Toxic Damage to the Myocardium and Systemic Hemodynamic Disorders in Acute Propranolol Poisoning in the Experiment - B. B. Yatsinyuk (Общая реаниматология)
Objective: to clarify the mechanisms underlying the development of systemic hemodynamic disorders in acute propranolol poisoning and possible ways of their correction. Materials and methods. The experiments were carried out on 40 male rats in 4 groups: 1) intact animals (n=10); 2) animals receiving propranolol in a dose of 1 mg/100 g body weight (n=10); 3) those receiving the drug in a dose of 2 mg/100 g body weight (n=10); 4) animals given noradrenaline in a single dose of 0.006 mg/100 g body weight 20 min after acute poisoning by propranol (2 mg/100 g body weight) (n=10). After administration of calypsol in a dose of 100 mg/kg body weight, the investigator catheterized the carotid artery to measure blood pressure (BP) (mm Hg) and the jugular vein to estimate central venous pressure (CVP) (cm H2O). An integral rheogram was recorded and stroke output (^l), cardiac output (CO) (ml/min), and total peripheral vascular resistance (TPVR) (103 din^s^cm-5) were calculated during 60 min. ECG was recorded. At min 60 of poisoning, blood samples were taken and estimated for the levels of glucose, lactate, pyruvate, and uric acid to determine the level of metabolic changes. The serum activity of enzymes, such as aspartate aminotransferase, lactate dehydrogenase, and cre-atine kinase MB fraction, was evaluated. The rate of free radical oxidation processes was estimated by the plasma chemilumines-cence technique. After the end of the experiment, the rats were killed by decapitation under calypsol anesthesia. The hearts were removed and fixed in 10% neutral buffered formalin. 5-^m-thick hematoxylin and eosin-stained paraffin-embedded sections were examined on an Axio Cam MRcS digital video fixation microscope. Results. The administration of propranolol suppresses cardiac hemodynamics and causes respiratory depression in a dose-dependent manner. At the same time compensatory mechanisms are aimed at eliminating hemodynamic disorders and hypoxia. To increase the dose of propranolol results in rapid circulatory decompensation, as suggested by the changes in heart rate, BP, TPVR, CVP, and CO. With smaller propranol doses (Group 2), BP is maintained by a less pronounced decrease in TPVR. Worse provision of O2 and oxidation substrates to tissues causes their metabolic disturbances and generalized cell damage — a change in the levels of carbohydrate metabolites, enzymes, and chemiluminescence values. Noradrenaline-induced stimulation of o^-adrenoceptors in the heart stabilizes hemodynamics and the analyzed biochemical parameters. Conclusion. When injected intraabdominally in a single dose of 1 and 2 mg/100 animal body weight, propranolol causes dose-dependent changes in systemic hemodynamics, respiration, carbohydrate metabolites, blood enzyme levels, and the activity of prooxidant and antioxidant systems. Noradrenaline-induced stimulation of 0^-adrenoceptors in the heart stabilized systemic hemodynamics, the values of plasma chemiluminescence, the activity of enzymes, and the level of carbohydrate metabolites. Key words: poisoning, experiment, propranolol, myocardium, systemic hemodynamics.